Phosphorus Deficiency Inhibits Cell Division But Not Growth in the Dinoflagellate Amphidinium carterae - Li, Meizhen; Shi, Xinguo; Guo, Chentao; Lin, Senjie (Frontiers in Microbiology, 2016)
Phosphorus (P) is an essential nutrient element for the growth of phytoplankton. How P deficiency affects population growth and the cell division cycle in dinoflagellates has only been studied in some species, and how it affects photosynthesis and cell growth remains poorly understood. In the present study, we investigated the impact of P deficiency on the cell division cycle, the abundance of the carbon-fixing enzyme Rubisco, and other cellular characteristics in the Gymnodiniales peridinin-plastid species Amphidinium carterae. We found that under P-replete condition, the cell cycle actively progressed in the culture in a 24-hour diel cycle with daily growth rates markedly higher than the P-deficient cultures, in which cells were arrested in the G1 phase and cell size significantly enlarged. The results suggest that, as in previously studied dinoflagellates, P deficiency likely disenables A. carterae to complete DNA duplication or check-point protein phosphorylation. We further found that under P-deficient condition, overall photosystem II quantum efficiency (Fv/Fm ratio) and Rubisco abundance decreased but not significantly, while cellular contents of carbon, nitrogen, and proteins increased significantly. These observations indicated that under P-deficiency, this dinoflagellate was able to continue photosynthesis and carbon fixation, such that proteins and photosynthetically fixed carbon could accumulate resulting in continued cell growth in the absence of division. This is likely an adaptive strategy thereby P-limited cells can be ready to resume the cell division cycle upon resupply of phosphorus.